CMET-34. IMPROVEMENT OF LEPTOMENINGEAL DISEASE FOLLOWING INFECTIOUS MENINGITIS. (11th November 2019) - Metrus, Nicholas; Kamiya, Carolos; Weathers, Shiao-Pei; Seligman, Christa; O'Brien, Barbara
Abstract: INTRODUCTION: The incidence of leptomeningeal disease (LMD) is increasing, due to better imaging, earlier diagnosis and improved systemic disease control. However, many of the systemic therapies do not cross the blood brain barrier (BBB) and, despite treatment with radiation and/or intrathecal (IT) chemotherapy, median survival is approximately 4-6months in solid tumors complicated by LMD. Repeated IT injections increase the risk of CNS infection. Preclinical models have shown that infectious meningitis transiently modifies the BBB. METHODS: Our series consisted of 6 LMD patients (5 breast cancer primary, 1 lung cancer primary) treated on IT chemotherapy at MD Anderson Cancer Center between 2013 and 2018, who subsequently developed infectious meningitis. Three patients had history of parenchymal metastases in addition to LMD and four had history of radiation to brain and/or spine. LMD was confirmed by cytology and/or imaging. All were treated with IT topotecan. RESULTS: CSF cultures were positive for Proprionobacterium acnes in three patients, Pseudomonas aeruginosa in two, and Raoultella ornithinolytica in one, who died shortly thereafter. Antibiotic regimens were variable. Three patients went on to receive IT chemotherapy post-infection (two never discontinued IT chemotherapy throughout infection). Those that had IT chemotherapy post-infection cleared CSF and imaging findings of LMD or maintained stability of radiographic LMD burden until death. No patients died directly from LMD. One patient, who developed infection after Ommaya placement and was never initiated on IT chemotherapy, still cleared his CSF of malignant cells. Excluding the patient who died shortly after meningitis diagnosis, the average time from meningitis diagnosis to death was 8.8 months and the average median survival from LMD diagnosis to death was 14 months. CONCLUSION: Our findings support further evaluating the safety and timing of IT chemotherapy with active infectious meningitis and the potential synergistic benefit of increased immunogenicity and chemotherapy in LMD.